INTEGRATED CONCEPTUAL STUDY OF RESERVOIR PERFORMANCE, SURFACE FACILITIES DESIGN, AND ECONOMIC ANALYSIS OF GAS-CONDENSATE RESERVOIR PRODUCING CO2 AND H2S - SUDARWOTO (NIM: 22208026), RINALDI
This research presents a comprehensive study in handling two impurities, CO2 and H2S, from a gas-condensate reservoir that includes reservoir performance study, surface facilities design, and economic analysis. Moreover, several sensitivity studies are applied to the reservoir model, designed surface facilities, and economic calculations. The result obtained from the base case scenario for reservoir performance study is the production of 25 MMSCFD gas for 13.2 years of production and 79.8% gas recovery. Sensitivity results show that the changes in plateau period and gas recovery are affected by the changes in gas-oil relative permeability. The designed surface facilities are capable of removing H2S levels up to ~ 100%, eliminating the CO2 content of up to 97.9%, lowering the water content up to 98.2%, and increasing the BTU content, in this case is GHV, from natural gas up to 34.4%. [CO2]out equations, which have 0,17% to 9,91% error, are derived from sensitivity study of pressure, temperature, and flow rate. Economics analysis calculation results show that the base case scenario is able to meet the market demand for gas production for 13 years by providing projected NPV of U.S. $ 31,133,300 with an IRR of 30.19% and 3.32 PBP years after production.